Dietary Salba (Salvia hispanica L) seed rich in α-linolenic acid improves adipose tissue dysfunction and the altered skeletal muscle glucose and lipid metabolism in dyslipidemic insulin-resistant rats - Oliva, Maria Eugenia (2013)
This work reports the effect of dietary Salba (chia) seed rich in n-3 -linolenic acid on the morphological and metabolic aspects involved in adipose tissue dysfunction and the mechanism/s underlying the impaired glucose and lipid metabolism in the skeletal muscle of rats fed a sucrose-rich diet (SRD). Rats were fed a SRD for 3 months. Thereafter, half the rats continued with SRD while in the other half, corn oil (CO) was replaced by chia seed for 3 months (SRD+chia). In control group, corn starch replaced sucrose. The replacement of CO by chia seed in the SRD reduced adipocyte hypertrophy, cell volume and size distribution, improved lipogenic enzyme activities, lipolysis and the antilipolytic action of insulin. In the skeletal muscle lipid storage, glucose phosphorylation and oxidation were normalized. Chia seed reversed the impaired insulin stimulated glycogen synthase activity, glycogen, glucose-6-phosphate and GLUT-4 protein levels as well as insulin resistance and dyslipidemia.